Response of a Specialist Bat to the Loss of a Critical Resource - Chaverri Echandi, Gloriana (2011)
Human activities have negatively impacted many species, particularly those with unique traits that restrict their use of resources and conditions to specific habitats. Unfortunately, few studies have been able to isolate the individual and combined effects of different threats on population persistence in a natural setting, since not all organisms can be associated with discrete habitat features occurring over limited spatial scales. We present the results of a field study that examines the short-term effects of roost loss in a specialist bat using a conspicuous, easily modified resource. We mimicked roost loss in the natural habitat and monitored individuals before and after the perturbation to determine patterns of resource use, spatial movements, and group stability. Our study focused on the disc-winged bat Thyroptera tricolor, a species highly morphologically specialized for roosting in the developing furled leaves of members of the order Zingiberales. We found that the number of species used for roosting increased, that home range size increased (before: mean 0.14±SD 0.08 ha; after: 0.73±0.68 ha), and that mean association indices decreased (before: 0.95±0.10; after: 0.77±0.18) once the roosting habitat was removed. These results demonstrate that the removal of roosting resources is associated with a decrease in roost-site preferences or selectivity, an increase in mobility of individuals, and a decrease in social cohesion. These responses may reduce fitness by potentially increasing energetic expenditure, predator exposure, and a decrease in cooperative interactions. Despite these potential risks, individuals never used roost-sites other than developing furled leaves, suggesting an extreme specialization that could ultimately jeopardize the long-term persistence of this species' local populations.